CRISPR-Cas systems feature and targeting phages diversity in Lacticaseibacillus rhamnosus strains - Panahi, Bahman; Dehganzad, Behnaz; Nami, Yousef (Frontiers in Microbiology, 2023)
One of the most important adaptive immune systems in bacteria against phages is clustered regularly interspaced short palindromic repeats (CRISPR) and CRISPR-associated (CAS) genes. In this investigation, an approach based on genome mining was employed to characterize the CRISPR-Cas systems of Lacticaseibacillus rhamnosus strains. The analysis involved retrieving complete genome sequences of L. rhamnosus strains, and assessing the diversity, prevalence, and evolution of their CRISPR-Cas systems. Following this, an analysis of homology in spacer sequences from identified CRISPR arrays was carried out to investigate and characterize the range of target phages. The findings revealed that 106 strains possessed valid CRISPR-Cas structures (comprising CRISPR loci and Cas genes), constituting 45% of the examined L. rhamnosus strains. The diversity observed in the CRISPR-Cas systems indicated that all identified systems belonged to subtype II-A. Analyzing the homology of spacer sequences with phage and prophage genomes discovered that strains possessing only CRISPR-Cas subtype II targeted a broader spectrum of foreign phages. In summary, this study suggests that while there isn't significant diversity among the CRISPR-Cas systems identified in L. rhamnosus strains, there exists notable variation in subtype II-A systems between L. rhamnosus and other lactobacilli. The diverse nature of these CRISPR-Cas systems underscores their natural activity and importance in adaptive immunity.